ASSESSMENT OF RELATIONSHIP BETWEEN SPHENOOCCIPITAL SYNCHONDROSIS AND CONDYLAR CORTICATION IN CHRONOLOGIC AGE DETERMINATION USING CBCT: A RETROSPECTIVE ANALYSIS - PARTHASARATHY, SHRUTHI; THIRUPPATHI, MANIGANDAN; P, MADHAVAN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Age estimation is of prime importance for personal identification during mass disasters and determination of legal age. Although many methods using other body parts are present, the whole body is not always available at the time of postmortem. Hence there is a constant demand for identifying newer methods to accurately determine age. Hence this study aims to evaluate the relationship between chronological age, sphenooccipital synchondrosis fusion and condylar cortication using CBCT. Methodology: CBCT scans of 75 patients between 10 to 25 years were evaluated. The CBCT images were evaluated in sagittal sections for the fusion status of sphenooccipital synchondrosis using a four stage grading system and fusion status of both condyles using a three stage grading system. Statistical analysis was performed using IBM SPSS software version 16. Results: In condylar cortication, the smallest mean age (14.73) was seen in type 1 and the largest mean age (21.50) was seen in type 3 which showed a statistically significant difference. However the left and right condyle did not show any difference in cortication. In SOS fusion stages, the mean age of 14.14, 16, 17.84 and 21.26 was found in stage 0, 1, 2 and 3 respectively. There was a steady increase in the stages with age which was highly significant. Conclusion: There is a strong positive correlation between chronological age, degree of SOS fusion stage and condyle cortication type. Condyle cortication can be used as an efficient alternative if the skull base is not intact at the time of forensic examination.